Corporate social responsibility in peer-to-peer accommodation: a focus on Airbnb - Farmaki, Anna; Kladou, Stella; Ioannides, Dimitri (My University, 2023)
Purpose: This paper aims to provide a critical synthesis of the interface of corporate social responsibility (CSR) and peer-to-peer (P2P) accommodation to offer insights that contribute to theory and practice of CSR in hospitality. Design/methodology/approach: By using key CSR models, this paper reflects on the nexus between CSR and P2P accommodation (with a focus on Airbnb) to identify opportunities and challenges with regard to CSR implementation in P2P accommodation and, thereby, progress the research agenda on the topic. Findings: This contribution will hopefully enable policymakers to improve the accountability of stakeholders related to P2P accommodation in terms of the sector’s impacts on local communities while contributing to the progression of the research agenda on CSR in hospitality. Research limitations/implications: Because this contribution is meant to be a “critical reflection paper”, the main purpose is to flesh out a commentary offering recommendations on how to account for CSR in relation to P2P accommodation and primarily Airbnb. As such, this paper aims to prompt future empirical research on the topic. Naturally, the major downside of this type of paper is the lack of an empirical approach. Practical implications: This paper advances theory on hospitality-related CSR, enabling policymakers to improve the stakeholders’ accountability related to P2P accommodation in terms of the sector’s impacts on local communities. Originality/value: Despite the increasing importance of CSR in hospitality, minimal academic attention has been paid insofar to CSR in the P2P accommodation sector. This inattention is surprising given the rapid expansion of the sector which, in turn, has imposed significant pressures on local communities.
Keywords: Airbnb; CSR; Peer-to-peer accommodation; Sustainability